2007
DOI: 10.1111/j.1440-1843.2007.01062.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of the onset of symptoms, Tuberculin test anergy and Kveim positive reaction in a large cohort of patients with sarcoidosis

Abstract: The onset of the symptoms was most frequent in spring and least frequent in the second half of the year (summer or autumn) in patients with sarcoidosis, Tuberculin anergy and a positive Kveim reaction. The significance of this finding in relation to aetiology and clinical utility needs to be further assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 13 publications
1
13
0
2
Order By: Relevance
“…peripheral anergy is typically confi ned to those with active sarcoidosis and is shown to be a sensitive and specifi c marker of disease acitivity. 43 In keeping with previous reports, patients with active pulmonary sarcoidosis exhibited peripheral anergy to mycobacterial (primarily TLR2) antigens 44,45 and TLR9 ligands 46 ( Figs 5A, 5B ). Mycobacterial antigens are of particular interest, as investigations have confi rmed their presence in diseased sarcoidosis tissue, 47 presumably relating to impaired antigen clearance, 48 and it is not alter the expression of a 7 nAChR, suggesting that tachyphylaxis relating to changes in receptor density did not occur.…”
Section: Peripheral Anergy To Specifi C Tlr Ligands In Symptomatic Pasupporting
confidence: 84%
“…peripheral anergy is typically confi ned to those with active sarcoidosis and is shown to be a sensitive and specifi c marker of disease acitivity. 43 In keeping with previous reports, patients with active pulmonary sarcoidosis exhibited peripheral anergy to mycobacterial (primarily TLR2) antigens 44,45 and TLR9 ligands 46 ( Figs 5A, 5B ). Mycobacterial antigens are of particular interest, as investigations have confi rmed their presence in diseased sarcoidosis tissue, 47 presumably relating to impaired antigen clearance, 48 and it is not alter the expression of a 7 nAChR, suggesting that tachyphylaxis relating to changes in receptor density did not occur.…”
Section: Peripheral Anergy To Specifi C Tlr Ligands In Symptomatic Pasupporting
confidence: 84%
“…For example, the highest incidence of sarcoidosis was observed in the winter in Olmsted County, MN [18] while a study from India observed the highest incidence in the summer and the lowest incidence in the winter [19]. Another study from Turkey observed the peak incidence in the spring [20]. Possible explanations for the geographic variation include different environmental exposures and availability of sunlight [3, 18, 20].…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies on the seasonality of sarcoidosis have yielded conflicting results. [1][2][3][4][5] …”
Section: Introductionmentioning
confidence: 99%